Wheat seedling emergence estimated from seed analysis (Scientia Agricola, 2011)
There are various vigor tests for the evaluation of seeds physiological quality, however, few studies correlate this tests with plants emergency. This study aimed at identifying wheat (Triticum aestivum L.) seed analysis variables that best predict seedling emergence. Wheat seeds (CEP 30 cultivar) were divided into two batches, one initially subjected to the accelerated ageing process and forming the low-quality batch, and the other, without application of the accelerated ageing process, to compose a high-quality batch. The following seed test variables were evaluated: (i) percentage of normal seedlings in the germination tests, (ii) initial germination counting, (iii) accelerated ageing, (iv) cold test without soil, (v) germination speed index, and (vi) emergence of seedlings in sand after seven and 15 days. The following seedling characteristics were evaluated: root and shoot lengths, total length, and dry mass of the root and shoot. The characteristics evaluated for the seedlings were subjected to path analysis and the seed tests variables to stepwise multiple regression analysis, taking seedling emergence at seven days as the response variable. Factor analysis was also carried out on all variables. Dry mass of the shoot and root length presented the best correlation with seedling emergence for the high-quality batch, but this behavior was not observed for any variable in the low-quality batch. Accelerated ageing was the best seedling emergence estimator for both batches of the used cultivar.